A comprehensive analysis of multi-circulatory disorders in early pressure injury and their diagnostic significance in rat models - Lu Chen; En Takashi; Akio Kamijo; Daiji Miura; Jian Lu; Lan Zhang; Hirotomo Ten; Jianglin Fan (Scientific Reports, 2023)
Abstract Early pressure injury (PI) progression is associated with multi-circulatory disorders and they interplay with each other, resulting in a lack of a satisfactory diagnostic method. We generated early PI and blanchable erythema hairless rat models. Transparent disc method and capillary refilling time test (CRTT) results were recorded with ultraviolet camera to capture the dynamics changes, and the blanching index and refilling index were set for comprehensive analysis. The deteriorated areas of early PI showed non-blanchable erythema (NBE) and an increase in erythema at 0.5 and 6 h with the transparent disc method. CRTT showed a marked refilling delay at 12 h. The comprehensive analysis of blanching index and refilling index showed a significant change in erythema from NBE at 0.5 h and ischemia progressing to hemorrhage at 18 h. There was also a marked difference in the deteriorating and improving areas within the same erythema. Pathological analysis showed inflammatory cell infiltration, with marked edema accompanied by increased hemorrhage and tissue necrosis. Furthermore, small arteries and veins with thrombosis and microthrombi were observed. Consistent ischemia after decompression and subsequent hemorrhage are important indicators, and comprehensive analysis can help increase the positive diagnosis rate over that for other circulatory disorders alone.